THE PROPULSION OF ENVIRONMENTAL HEALTH TO PROMOTE A HEALTHY CITY THROUGH THE COORDINATION OF THE NETWORK OF VILLAGE HEALTH VOLUNTEER LEADERS, PUBLIC AND PRIVATE ORGANIZATIONS: WAT KAEW SUBDISTRICT HEALTH PROMOTION HOSPITAL - Chantorn, Chaiyaporn (Journal of MCU Nakhondhat, 2024)
This research aims to: 1) Evaluate the results of promoting environmental health towards healthy cities among village public health volunteers together with a network of village public health volunteer leaders, and public and private organizations, and 2) Create a plan to promote environmental health, towards a healthy city of village public health volunteers together with a network of village public health volunteer leaders, public and private organizations, involved people select people who are willing and volunteer to participate in the research project, consisting of 20 people of Community Health Development Network, i.e., 14 village health volunteer leaders, at least 3 government organizations such as sub-district service organizations, community development organizations, sub-district health hospitals, and at least 3 private organizations such as store operators and establishment and business organizations. Quantitative data were collected using assessments and questionnaires (IOC = 0.867, r = 0.85). Analyze data with basic statistics Qualitative data were collected through document analysis, observation, interviews, and focus groups. Data were analyzed using content analysis. The research found that: The community provides a context for a healthy environment. and the evaluation results of driving the environmental health promotion plan towards a healthy city were at a high level, there were the policy to promote a healthy environment, promote communities to be livable cities and promote health through community networks to the public to be knowledgeable about good health in all age groups. 2) The developed plan, named the plan "Volunteers do good deeds with the heart, join forces together to promote environmental health in Wat Kaew Subdistrict towards a healthy city", It was an activity that promotes environmental health, people in the community were interested in joining the activities, with happiness expressed from a smile, and 3) Satisfaction in driving environmental health promotion work towards a healthy city through the coordination of the network of village health volunteer leaders, public and private organizations is at the highest level.